2018
DOI: 10.1177/1474515118800099
|View full text |Cite
|
Sign up to set email alerts
|

Development and effects of a self-management efficacy promotion program for adult patients with congenital heart disease

Abstract: The self-management efficacy promotion program for adults with congenital heart disease had a significant effect on disease-related knowledge and self-management implementation, but did not affect health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Considering that PHC is akin to self-efficacy and there is evidence that self-efficacy can be improved for individuals with cardiovascular disease through cardiac rehabilitation programs, 28,29 it is possible that these methods might also translate to improving patients' PHC. A recent study by Lee and colleagues, 30 in 2019, reported that a six-week self-management efficacy promotion program among adults with CHD improved disease-related knowledge and self-management performance, but did not increase healthrelated quality of life. However, authors did not report examining differences specifically in Psychosocial health, ASR: Adult Self-Report (ages 18+ years); HADS: Hospital Anxiety and Depression Scale; NYHA: New York Heart Association; PHC: Perceived Health Competency; T1: baseline; T2: three-year follow-up; YSR: Youth Self-Report (ages 15-17 years).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that PHC is akin to self-efficacy and there is evidence that self-efficacy can be improved for individuals with cardiovascular disease through cardiac rehabilitation programs, 28,29 it is possible that these methods might also translate to improving patients' PHC. A recent study by Lee and colleagues, 30 in 2019, reported that a six-week self-management efficacy promotion program among adults with CHD improved disease-related knowledge and self-management performance, but did not increase healthrelated quality of life. However, authors did not report examining differences specifically in Psychosocial health, ASR: Adult Self-Report (ages 18+ years); HADS: Hospital Anxiety and Depression Scale; NYHA: New York Heart Association; PHC: Perceived Health Competency; T1: baseline; T2: three-year follow-up; YSR: Youth Self-Report (ages 15-17 years).…”
Section: Discussionmentioning
confidence: 99%
“…High self‐efficacy has been found to be positively associated with disease management, psychological well‐being, 6 quality of life 21 and adherence to medication, diet and exercise 22,23 among people with CVD. In addition, high self‐efficacy was found to predict changes in lifestyle concerning the risk factors and behavioural modification in chronic heart diseses 16‐18,24,25 . Low self‐efficacy has been associated with poor management of illness, coping strategies in dealing with disease, and poor health status including high symptom burden and a lower quality of life among people with coronary heart disease 7,25,26 …”
Section: Introductionmentioning
confidence: 99%
“…In the European Journal of Cardiovascular Nursing there have been several studies investigating the effects of complex interventions, such as self-management programs for chronic conditions, 24 tele-rehabilitation after hospital discharge, 5,6 complementary methods for symptom management, 7 and interventions utilizing peer support for postoperative recovery. 8 The ultimate goal of these complex interventions is to achieve a meaningful and sustainable change of clinical practice.…”
Section: The Problem: Complex Interventions = ‘Black Boxes’?mentioning
confidence: 99%